Ratio between Right Ventricular Longitudinal Strain and Pulmonary Arterial Systolic Pressure: Novel Prognostic Parameter in Patients Undergoing Cardiac Resynchronization Therapy - Deaconu, Silvia (J Clin Med, 2021)
Background: We aimed to evaluate whether right ventricle (RV) longitudinal strain indexed to pulmonary arterial systolic pressure (PASP) has prognostic significance in patients undergoing cardiac resynchronization therapy (CRT). Methods: Patients undergoing CRT were prospectively included. The primary endpoint was adverse cardiovascular events (death and HF-related hospitalizations). RV global longitudinal strain (RVGLS) and RV free wall strain (RVfwS) were measured by speckle tracking and indexed to echocardiographic estimated PASP. Results: A total of 54 patients (64.0 ± 13.8 years; 58% male) were included. After 33 ± 12.9 months, the primary endpoint occurred in 18 patients. Baseline RVGLS/PASP and RVfwS/PASP showed good discriminative ability for response to CRT (AUC = 0.88, 95% CI (0.74–1) and AUC = 0.87, 95% CI (0.77–1)). RVGLS/PASP and RVfwS/PASP were significantly associated with high risk of events at univariate analysis (HR 0.039, 95% CI (0.001–0.8) p < 0.05, respectively HR = 0.049, 95% CI (0.0033–0.72), p < 0.05). Upon multivariate Cox regression analysis, RVGLS/PASP and RVfwS/PASP remained associated with high risk of events (HR 0.018, 95% CI (0.0005–0.64), p = 0.02 and HR 0.015, 95% CI (0.0004–0.524), p = 0.01) after correction for gender, etiology, QRS duration and morphology. Conclusions: Indexing RV longitudinal strain (global and free wall) by PASP provides a parameter, which independently identifies patients with high risk of cardiovascular events and predicts non-response to CRT.